Des monuments à l’histoire : la raison des ruines et Michel de Montaigne - Schnapp, Alain (Hyperboreus, 2021)
Michael Rostovtzev was among the few scholars of the 20th century to dominate the sometimes conﬂicting, or feeble at least, connections between history and archaeology. By questioning Michel de Montaigne’s curiosity for Roman antiquities and his critical lecture of the antiquary works, this paper intends to demonstrate how Montaigne has led the foundations of an epistemology of Antiquity that anticipated the research and works of the Russian master.